Resolution Enhanced of GRBR Observation-Based Ionospheric Tomography in Indonesia - Manik, Timbul; Purwono, Adi; Lathif, Musthofa; Batubara, Mario; Yamamoto, Mamoru (Proceeding International Conference on Science and Engineering, 2019)
An ionospheric tomography reconstruction using Algebraic Reconstruction Technique (ART) method has been successfully carried out recently. Data utilized on this work was a campaign-based Gnu-Radio Beacon Receiver (GRBR) observation in West Java during 8-10 November 2016 and 25-29 September 2017 data. Grid resolution of the tomography previously had been increased in the in the latitudinal (0.5o horizontal direction) and altitude (~25 km in vertical direction) scales. Although the quality of the tomography has also met a compatibility level through the correlation analysis (e.g. 85% of correlation coefficient), the computation result should be improved in order to get the best value of bias frequency (i.e. < 1 MHz). Through this opportunity, the result of the tomography within the grid resolution of 0.5o and ~25 km for the latitude and altitude respectively is presented.